Nurses’ interventions to promote cancer patient engagement and related outcomes: a systematic review and meta-analysis protocol - Bonetti, Loris; Tolotti, Angela; Valcarenghi, Dario; Graffigna, Guendalina; Nania, Tiziana; Sari, Davide; Ferri, Paola; Barello, Serena (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Due to the ageing of cancer patients, new approaches that requirea more active participation in the self-management of cancer treatment at home are needed. Nurses are strategic in improving the patient’s engagement capability in this regard. Knowing which interventions are more effective for the promotion of patient engagement could be useful to improve the effectiveness of the care provided. Therefore, this study aims to systematically review nursing interventions or programs that promote patient engagement in oncological nursing care and summarizing the main evidence related to their impact on relevant clinical and psychosocial outcomes. Method. This is a systematic review and meta-analysis protocol based on Cochrane Handbook for the systematic review of interventions. We will search the most important electronic databases (PUBMED, CINAHL, EMBASE, SCOPUS, ISI Web of Science, Cochrane library) to find out which patient engagement interventions (active adult patient involvement) are implemented in oncological settings and understand what is the effectiveness of these interventions on the outcomes reported in the literature. The GRADE methodology will be used to synthetize the evidence. If possible, also a meta-analysis will be performed. We registered the study protocol on the PROSPERO database (N° CRD42020146189). Discussion and Conclusion. To our knowledge, this is the first systematic review to address this clinical question in the field of oncology. This review will offer health professionals indications on the most frequently adopted patient engagement interventions and verify their clinical effectiveness. Furthermore, any gaps in the scientific literature will be highlighted.